The effectiveness of study group guidance to improve learning motivation of elementary school students - Ketut Susiani; Nengah Suastika; I Wayan Lasmawan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
Guidance and counseling in elementary schools are intended to help students develop various potentials within themselves so that they are able to have good adjustments to assignments and learning activities, so as to achieve high academic achievement. Tutoring for school students one of which is oriented to develop student learning motivation. High learning motivation encourages students to achieve optimal learning achievement. This study aims to analyze the effectiveness of the use of group guidance to increase student motivation in elementary schools. This study uses pre-experimental study with one-group pre-test-posttest design. The research subjects were elementary school students with a sample of 40 students. The research data was collected through a learning motivation questionnaire. Data analysis was carried out descriptively and hypothesis testing through paired sample t-test. The results of descriptive data analysis showed that students learning motivation increased from before participating in group guidance learning which was in the medium category to high after participating in group guidance learning. These results are also supported by the results of the t-test analysis which shows that there are significant differences in learning motivation between before and after following group guidance. This shows that tutoring with group guidance techniques is effective in increasing the learning motivation of elementary school students. The implication of this results research to elementary school guidance and counseling program were discussed.